The indexical nature of classroom discourse: the role of technology integration. Issue 1 (2nd January 2020) - Jadallah, May; Kang, Hyun-Sook; Hund, Alycia M.; Kirby, Elizabeth M.
ABSTRACT: This study explored how fifth-grade teachers and their students use indexical expressions (i.e. verbal expressions to convey the degree of certainty or tentativeness) as being indicative of dialogism in whole-class discussions in four elementary classes. Half of the classes received instruction on geographic information system (GIS)-related topics by way of technology integration and inquiry-based instruction, whereas the other half received typical social-studies lessons involving paper maps, serving as a baseline group. Technology integration was associated with relatively more use of indexical expressions, both boosters (to convey certainty) and hedges (to denote tentativeness), by teachers and their students and higher impact of student language on teacher language in the degree of absoluteness and tentativeness. Moreover, whereas the network of indexical expressions in the technology-integrated classes included a reciprocal impact between teachers and students and among students, the network in the baseline classes was limited to student-student exchanges alone. These findings suggest that technology integration in inquiry lessons tends to encourage the use of tentative and confirmatory language that aligns with the nature of the discipline.